Laminin-5 γ2 Chain Expression Correlates with Unfavorable Prognosis in Colon Carcinomas - C. Lenander; J. K. Habermann; Å. Öst; B. Nilsson; H. Schimmelpenning; K. Tryggvason; G. Auer (Analytical Cellular Pathology)
Expression of the γ2 chain at the invasive front of different tumors has indicated an important role for laminin-5 in cell migration during tumor invasion and tissue remodeling. As there is considerable need for reliable invasion and prognostic markers we evaluated the correlation of laminin-5 γ2 chain expression with clinicopathologic parameters and patient survival in 93 primary colon carcinomas. Epithelial cells of normal mucosa were consistently negative for staining. In contrast, positive cytoplasmic staining was observed in 89 tumors (96%). Twenty-four (26%) cases were scored as sparse, 34 (37%) as moderate, and 31 (33%) as frequent γ2 chain expression. There was a significant association of laminin-5 γ2 chain expression and local invasiveness of colon carcinomas according to Dukes stage (A-C) (p = 0.001) and tumor budding (p < 0.001). A statistical significance could also be noted in decreasing tumor differentiation (p < 0.001) and correlation to tumor size (p = 0.032). No correlation was observed to tumor site. Univariate analysis identified laminin-5 (p = 0.010), tumor differentiation (p = 0.006) and Dukes grade (p < 0.001) as significant variables in predicting prognosis. However, by multivariate analyses, this study could not demonstrate that laminin-5 γ2 chain expression is an independent predictive factor for survival. The results indicate that laminin-5 γ2 chain expression is up-regulated during the progression of human colon cancer and that it plays a role in the aggressiveness of these tumors. Demonstration of laminin-5 γ2 chain positivity also facilitates detection of individual cells or minor cell clusters invading the surrounding stroma.